The impact of waste types in supporting lean manufacturing principles (a field study in Jordanian pharmaceutical companies) - Jamal Ahmed Hamad (The Scientific Journal of Cihan University– Sulaimaniya, 2017)
In the last few years, the importance of lean manufacturing has increased, so many industrial companies are paying great attention to their principles in order to achieve the customer added value and improve the competitive position by increasing productivity, eliminating waste or reducing it; increasing quality and reducing costs. So the research will shed some light on the concept and importance of lean manufacturing and its basic principles especially the waste and how to eliminate it. The research main objective is to determine the effect of waste on the basic principles of the leanmanufacturing in the Jordanian pharmaceutical companies. The aim of the research is to provide theoretical features for the companies under discussion about the concept and importance of lean manufacturing and their impact on waste to achieve the lean manufacturing.